The paradoxes of Brazil in XXI century ¿regional leader and global player? - Lechini, Gladys (2011)
This essay critically analyzes Brazil’s multilateral politics, suggesting that Brazil acts in a two-fold way and under differentiated strategies. On the one hand, the country presents itself as an emerging regional leader On the other, Brasil plays the role of a middle-range power in South America, and in particular in MERCOSUR, but this strategy does not necessarily implies leading processes and initiatives. The author proposes an interpretation of the Brazilian strategy.